Communication Behaviour of Forage Growing Farmers in Kandi Belt of Jammu Division - Shabnam Kundal, S.K. Kher, P.S. Slathia, Poonam Parihar; Vinod Gupta (Indian Journal of Extension Education, 2018)
Awareness and knowledge about improved technologies in Agriculture and allied can be upgraded through many information sources. Different strata of farmers use different types of information sources as per their socioeconomic status. Some farmers perceive fellow farmers, radio, television and newspapers as the main source of agricultural information while some perceive mass media useful to great extent in increasing agricultural production. In order to know the facts, a study was conducted in Samba and Kathua districts of Jammu division. From each district, three blocks were selected purposively and the final sample size consisted of 144 forage growing farmers. The study revealed that 68.05 per cent of the farmers had medium level (score 6-9) of information seeking behaviour. Only 9.70 per cent fall in high (score above 9) level of information seeking behaviour. Majorities (83.33%) of the respondents were in contact with neighbors and input agencies ‘sometimes’. There was no significant difference in the use of personal localite channels of the farmers in the two districts (Kathua and Samba). Junior Agriculture Extension officers were major source of information for about 70.83 per cent of the farmers. Overall 91.66 per cent of the farmers had never participated in any demonstration conducted by the development agencies. There was no significant difference in the use of personal cosmopolite channels of the farmers in the two districts (Kathua and Samba) as far as information seeking is concerned. Overall 72.91 per cent of the farmers in the two districts of Kathua and Samba watch T.V. always. However out of 105 respondents’ only five farmers watch agricultural programmes on T.V. always. Neighbours and Input agencies contributed equally (83.33%) each to the knowledge of forage grower in personal localite channels.